Sounds like Psychology to Me: Transgressing the Boundaries between Philosophy and Science. - Andreotta, Adam J. (Limina, 2016)
In recent years, some eminent scientists have argued that free will, as commonly understood, is an illusion. Given that questions such as 'do we have free will?' were once pursued solely by philosophers, how should science and philosophy coalesce here? Do philosophy and science simply represent different phases of a particular investigation--the philosopher concerned with formulating a specific question and the scientist with empirically testing it? Or should the interactions between the two be more involved? Contemporary responses to such questions have occasionally given rise to conflict amongst members of different disciplines. Some individual scientists have dismissed philosophical objections to their scientific theories on the grounds that the philosopher lacks experience in their respective field. And some individual philosophers have rejected scientific theories on a priori grounds, without giving due consideration to the empirical evidence. In this paper, I argue that such dismissiveness, on both sides, is mistaken. I will do so by putting forward a view that is inspired by the American philosopher and psychologist William James, who has been characterised by recent commentators as having performed 'boundary work'. Boundary work involves transgressing the dividing lines between such disciplines, and attempting to solve certain problems without being restricted to the methodology of a single discipline. To help support this position, I will examine a series of contemporary problems that are pursued in both philosophy and science that relate to moral responsibility and free will. I will argue that in order to solve such problems we need to perform boundary work.